Oxytocin administration during labor does not affect maternal serum oxytocin levels, early postpartum breastfeeding attitude and maternal attachment - Meryem Özdemir; Esin Çeber Turfan; Hüseyin Levent Keskin (PLoS ONE, 2025)
The goal was to investigate the effects of synthetic oxytocin administration during labor on maternal and neonatal serum oxytocin levels, early breastfeeding attitudes, and postpartum maternal attachment immediately after birth. This prospective case-control study was carried out in the delivery unit of a tertiary hospital. The pregnant women who were at term and had an uncomplicated low-risk single pregnancy were enrolled in this study. The cases that required receiving i.v. synthetic oxytocin during labor constituted the study group, who didn’t receive synthetic oxytocin were included in the control group. From the cases who gave birth vaginally and met criteria, maternal venous and umbilical cord blood samples were taken immediately after delivery. Serum oxytocin test analysis was performed using the Competitive ELISA method. The socio-demographic characteristics, obstetric history of mothers, and neonatal features were recorded from the medical records. Early breastfeeding attitude of mothers was assessed using the Breastfeeding Attitudes Evaluation Scale (BAES). The Maternal Attachment Scale (MAS) was used to evaluate the experiences, feelings, and emotions of mothers. p-value <0.05 was accepted as statistically significant. There is no difference between the age, other socio-demographic, clinical, and obstetric data of mothers in the study group (n = 75) and the control group (n = 78) (p > 0.05), except for the time to hold the baby for the first time (p = 0.016). The maternal serum mean oxytocin levels of the maternal and umbilical cord blood plasma oxytocin levels of their newborns were similar between the groups (p = 0.331, p = 0.475; respectively). No statistically significant difference was observed between the groups in the BAES scores and the MAS scores (p > 0.05). It was observed that intravenous synthetic administration during labor did not affect the maternal and neonatal serum oxytocin levels and had no effect on early breastfeeding attitude and maternal attachment.